2015
DOI: 10.1080/00103624.2015.1069319
|View full text |Cite
|
Sign up to set email alerts
|

Soil-Test-Based Optimum Fertilizer Doses for Attaining Yield Targets of Rice under Midland Alfisols of Eastern India

Abstract: Soil test crop response experiments on rice were conducted in Bastar plateau Agro-Climatic Zone of Chhattisgarh during 2009-2011 to assess yield, soil, plant and fertilizer nitrogen, phosphorus and potassium (NPK) nutrient relationships and calibrate optimum fertilizer doses for attaining yield targets. Soil fertility status was low to medium for N (194-283 kg ha -1 ) and P (7.53-19.66 kg ha -1 ), and medium to high for K (226-320 kg ha -1 ). Based on nutrient requirement (NR, kg q -1 ), contribution from soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Also, rice's higher grain yield response to N and K may be attributed to its high nutrient requirement. Our findings coincided with the observation of Sharma et al [29], who reported a close association between crop yields and nutrient uptake. Moreover, positive and significant correlations between grain yield and plant height (r = 0.87; p = <0.01), tiller number (r = 0.70; p = <0.01), panicle length (r = 0.74; p = <0.01), panicle weight (r = 0.73; p = <0.01), grain number panicle −1 (r = 0.80; p = <0.01), and straw yield (r = 0.74; p = <0.01) were observed.…”
Section: Grain Yieldsupporting
confidence: 93%
“…Also, rice's higher grain yield response to N and K may be attributed to its high nutrient requirement. Our findings coincided with the observation of Sharma et al [29], who reported a close association between crop yields and nutrient uptake. Moreover, positive and significant correlations between grain yield and plant height (r = 0.87; p = <0.01), tiller number (r = 0.70; p = <0.01), panicle length (r = 0.74; p = <0.01), panicle weight (r = 0.73; p = <0.01), grain number panicle −1 (r = 0.80; p = <0.01), and straw yield (r = 0.74; p = <0.01) were observed.…”
Section: Grain Yieldsupporting
confidence: 93%
“…Net returns from the improved practice (STCR technology) were substantially higher than the FP for DSR. Similarly, higher indices of economic analysis, such as gross and net return and benefit:cost ratio, than the GRD in transplanted rice under rainfed Alfisols have been noticed [15]. The highest economic efficiency was recorded with STCR TY2 (INR 285 ha −1 d −1 ), which was due to the highest net return being obtained under this treatment (Table 10).…”
Section: Fertilizer Economics and Economic Efficiencymentioning
confidence: 78%
“…Harnessing the potential yields of high yielding varieties of crops requires the application of optimum doses of nutrients [15]. However, an inadequate and imbalanced fertilizer use for crop production, without proper knowledge of the inherent soil capabilities and crop requirements, is also one of the causes that prevent gaining the full yield potential of crops and the deterioration of soil health, as well as economic losses to farmers [8,16], and often resulting in an adverse impact on crops and the soil, in terms of nutrient toxicity and deficiency [8].…”
Section: Introductionmentioning
confidence: 99%
“…It was estimated that 55% of the increase in food comes from the influence of fertilizers [12]. However, it was known that 2 /3 of used N fertilizer can be lost through washing, evaporation, denitrification, and carried away by runoff [13,14]; so that in rice cultivation, N efficiency is very low, like P fertilizers. After P nutrients is given, dissolution occurs.…”
Section: Plant Heightmentioning
confidence: 99%